Predictive value of net water uptake for early neurological deterioration after mechanical thrombectomy in acute ischemic stroke with large vessel occlusion - Kuang, Min; Li, Junying; Wang, Jian; Chen, Guangwen; Luo, Chao (Frontiers in Neurology, 2025)
PurposeTo investigate whether Net Water Uptake (NWU) can predict early neurological deterioration (END) after mechanical thrombectomy (MT) in acute ischemic stroke with large vessel occlusion (AIS-LVO).Materials and methodsWe retrospectively analyzed consecutive patients with AIS-LVO who underwent MT. Patients were categorized into the END group and the non-END group based on whether END occurred. NWU was an imaging parameter to quantify the water uptake capacity of brain tissue and measured on admission non-contrast computed tomography (NCCT). Early edema progression rate (EPR) was determined as the ratio of NWU and time from symptom onset to baseline imaging. Then, the baseline characteristics were subsequently collected. Variable and multiple regression analyses were performed to explore independent risk factors for END. Finally, receiver operating characteristic (ROC) curves were constructed to evaluate the predictive value of NWU for END.ResultsA total of 158 patients were included. The median NWU, admission National Institutes of Health Stroke Scale (NIHSS) and EPR in END group was 10.1% (IQR: 6.8–15.4), 16(IQR: 15–19) and 0.087% (IQR: 0.038–0.187). Respectively, the non-END group was 6.8% (IQR: 0–10.9), 13(IQR: 8–17) and 0.043% (IQR: 0–0.096). Compared with the non-END group, the END group had higher NWU (p = 0.004), higher admission NIHSS score (p = 0.001), and higher EPR (p = 0.006); multiple logistic regression showed that NWU (odds ratio [OR], 1.084; 95% confidence interval [CI], 1.004–1.171, p = 0.039) and admission NIHSS score (OR, 1.124; 95%CI, 1.032–1.224; p = 0.007) were independent risk factors for END. ROC curve showed that NWU had a moderate predictive ability for END. The area under the ROC curve (AUC) was 0.665 (95%CI, 0.561–0.770). The AUC of admission NIHSS score was 0.687 (95%CI, 0.698–0.776). NWU combined with admission NIHSS score had the highest predictive value for END, with an AUC of 0.739 (95%CI, 0.648–0.831).ConclusionThe NWU was an independent predictor of END and increased NWU is associated with END in patients with AIS-LVO after MT. Similarly, the admission NIHSS score was also an independent predictor. The combination of NWU and the admission NIHSS score achieves the strongest predictive ability for END.